Conceptual progression of K-10 student on the free-falling objects acceleration concept as an effect of E-CDCCText. Issue 1 (March 2021) - Setiono, I A; Suhandi, A; Liliawati, W
Abstract: The purpose of this study was to obtain the impact of using Electronic Conceptual Development Conceptual Change Text (E-CDCCText) related to the concept of acceleration of free-falling objects on K-10 students. E-CDCCText consists of seven parts. The third part is a conceptual development text. The fourth, fifth, and sixth parts are conceptual change text added with cognitive conflict and scientific explanation. The method used is pre-experiment with one group of three test designs. Research subjects were 32 K-10 students whose average age is 14-15 years old, consisting of 20 female and 12 male students in Yogyakarta. The research subjects were selected by random sampling techniques for the class. Data is collected based on parallel conception tests in the four-tier test format on the free-falling objects acceleration concept. These results indicate that E-CDCCText has high effectiveness in remediating misconceptions. In general, the use of E-CDCCText has been effective in facilitating the conceptual progression of students in the type of well progression (75%). The use of E-CDCCText does not cause gender bias between female and male students. E-CDCCText has been effective in facilitating the conceptual progression of female and male students in the type of well progression (75%). E-CDCCText can effectively use in conceptual development and conceptual changes activities on the free-falling objects acceleration concept.